Problematyka restrukturyzacji oraz wzrostu efektywności przedsiębiorstwa na przykładzie wybranych podmiotów sektora elektroenergetycznego w Polsce - próba podsumowania ostatnich lat reorganizacji przedsiębiorstw - Białowąs, Piotr (Problems of the Restructuring Process and Raising of the Effectiveness of an Enterprise Based on the Example of Chosen Enterprises in Polish Energy Industry - Summary of the Last Years' Restructuring Process, 2008)
In the article, the author presented directions of development of Polish enterprises in energy sector. The papers shows the main external law requirements concerning changes in Polish energy enterprises. Basing on the implemented into the Polish law European directive regulations concerning divided distribution and commercial sales area, the author presented the main restructuring scenarios for enterprises. The study compares the potential of Polish and West European enterprises. The Author proposed the optimal restructuring process for Polish energy enterprises, basing on his own experiences.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 20-45